Internal Auditor Performance of Minahasa Regency Government in Terms of Competence and Independence - Joseph Philip Kambey; Lenny L Evinita; Cecilia Lelly Kewo (Budapest International Research and Critics University, 2022)
There are three main aspects to had a good governance, namely supervision, control, and inspection. Supervision is carried out by parties outside the executive branch, namely the community and the DPR to oversee the government's performance. Control is a mechanism carried out by the executive to ensure that systems and policies are implemented properly, while inspection is an activity carried out by parties who have independence and professional competence to check whether the results of government performance are in accordance with standards. This research was conducted at the Minahasa Regency Inspectorate. The purpose of this study was to determine whether there is an influence of competence on the performance of internal auditors and whether there is an influence of independence on the performance of internal auditors in Minahasa Regency. The research method uses a quantitative approach. The sample is 46 auditors and data collection is done by giving questionnaires to respondents. The data that has been collected is then analyzed using multiple regression analysis techniques. The results showed that competence had a positive effect on the performance of internal auditors, as well as independence had a positive effect on the performance of internal auditors at the Minahasa inspectorate.